Evaluation of Stenting for Intracranial Internal Carotid Artery Stenosis Using Flow Reversal - Ishihara, Manabu; Matsuzaki, Kazuhito; Matsuda, Taku; Satoh, Koichi; Hanaoka, Mami (Journal of Neuroendovascular Therapy, 2018)
Objective: The safety of stenting for intracranial internal carotid artery stenosis using flow reversal embolic protection was evaluated.Subjects and Methods: Of the 13 patients who underwent stenting between April 2011 and September 2016, those treated with (group F) and without (group N) flow reversal were compared retrospectively.Results: An embolic complication was observed in one patient in the group N but none in the group F. The diffusion-weighted imaging (DWI)-positive rate was 0% in the F group.Conclusion: Stenting for intracranial internal carotid artery stenosis using flow reversal is a safe and effective procedure.